Rethinking law and violence - Vashist, Latika; Sood, Jyoti Dogra (New Delhi : Oxford University Press, 2020)
Conceptualized outside the theoretical framing of both liberal as well as critical approaches, this text re-imagines the law by exploring the contradictions and polarities of in terms of its relationship with violence. It encompasses and interweaves themes and ideas as diverse as death penalty, community might, state sovereignty on the one hand, to animal rights, sexual consent, children's agency and LGBT rights, on the other.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 23, 2020).
Keywords: Law -- India -- Philosophy; Violence -- India; Law; Jurisprudence & general issues